Hemodynamic performance limits of the neonatal Double-Lumen cannula - Rasooli, Reza; Jamil, Muhammad; Rezaeimoghaddam, Mohammad; Yıldız, Yahya; Salihoğlu, Ece; Pekkan, Kerem (Elsevier Ltd, 2021)
Venovenous extracorporeal membrane oxygenation (VV-ECMO) is the preferred surgical intervention for patients suffering from severe cardiorespiratory failure, also encountered in SARS-Cov-2 management. The key component of VV-ECMO is the double-lumen cannula (DLC) that enables single-site access. The biofluid dynamics of this compact device is particularly challenging for neonatal patients due to high Reynolds numbers, tricuspid valve location and right-atrium hemodynamics. In this paper we present detailed findings of our comparative analysis of the right-atrial hemodynamics and salient design features of the 13Fr Avalon Elite DLC (as the clinically preferred neonatal cannula) with the alternate Origen DLC design, using experimentally validated computational fluid dynamics. Highly accurate 3D-reconstructions of both devices were obtained through an integrated optical coherence tomography and micro-CT imaging approach. Both cannula configurations displayed complex flow structures inside the atrium, superimposed over predominant recirculation regimes. We found that the Avalon DLC performed significantly better than the Origen alternative, by capturing 80% and 94% of venous blood from the inferior and superior vena cavae, respectively and infusing the oxygenated blood with an efficiency of more than 85%. The micro-scale geometric design features of the Avalon DLC that are associated with superior hemodynamics were investigated through 14 parametric cannula configurations. These simulations showed that the strategic placement of drainage holes, the smooth infusion blood stream diverter and efficient distribution of the venous blood capturing area between the vena cavae are associated with robust blood flow performance. Nevertheless, our parametric results indicate that there is still room for further device optimization beyond the performance measurements for both Avalon and Origen DLC in this study. In particular, the performance envelope of malpositioned cannula and off-design conditions require additional blood flow simulations for analysis.
Keywords: Biofluid Mechanics; Cardiovascular Devices; Congenital Heart Defects; Hemodynamics; Hemolysis and Thrombogenicity; Micro-CT